Green ternary composite of graphitic carbon nitride/TiO2/ polyorthoanisidine for the enhanced photocatalytic treatment of Direct Red 28 for industrial water treatment solutions - Alkorbi, Ali S.; Gill, Nouman; Anjum, Muhammad Naveed; Saif, Muhammad Jawwad; Ahmad, Mirza Nadeem; Qadir, Muhammad Bilal; Khaliq, Zubair; Faisal, Mohd; Jalalah, Mohammed; Harraz, Farid A. (Frontiers in Chemistry, 2024)
Industrial dye effluent causes significant risks to the environment. The present study was focused on photocatalytic degradation of the dye Direct Red 28 using a ternary composite of graphitic carbon nitride, TiO2, and polyorthoanisidine (g-C3N4/TiO2/POA), prepared by in-situ oxidative polymerization o-anisidine. The synthesized composite g-C3N4/TiO2/POA properties were characterized using different analytical techniques. X-ray diffraction (XRD) results revealed the prominent pattern of TiO2 and g-C3N4 in the composite peak at 2θ° while Fourier transform infrared (FTIR) results provided the confirmation peaks for g-C3N4/TiO2/POA and POA at 1,110 cm−1 and 1,084 cm−1 for C-O-C ether. Scanning electron microscopy (SEM) demonstrated an increase in the average size of the composite up to 428 nm. The energy-dispersive X-ray spectroscopy (EDX) spectrum provided the weight percentages of the C, O, and Ti in the composite were 8.5%, 45.69%, and 45.81%, respectively. The photocatalytic degradation of Direct Red 28 dye under UV irradiation using a composite showed that 86% Direct Red 28 dye was degraded by a 30 mg/L dose of g-C3N4/TiO2/POA in 240 min at pH 2. After four consecutive cycles, the utilized composite showed 79% degradation of Direct Red 28, demonstrating the stability and effectiveness of the g-C3N4/TiO2/POA photocatalyst. The high reusability and efficiency of the g-C3N4/TiO2/POA composite are due to increased light absorption range and reduced e−/h+ recombination rate in the presence of g-C3N4 and POA.